Investigating the nuclear import protein KPnß€1 as a cancer therapeutic target - Ajayi-Smith, Aderonke Fopesaye (Department of Integrative Biomedical Sciences (IBMS), 2022)
The dysregulation of numerous genes has been associated with the development and progression of cancer, many of which are being investigated as potential therapeutic targets. Previous work in our laboratory and others reported the elevated expression of the nuclear import protein Karyopherin Beta 1 (Kpnβ1) in various cancers. The inhibition of Kpnβ1 by siRNA silencing inhibited the proliferation of cancer cells and induced cell death via apoptosis while having little effect on non-cancer cells. These findings suggested that Kpnβ1 has potential as an anti-cancer therapeutic target. Using an in silico screening approach to identify small molecule inhibitors of Kpnβ1 with anti-cancer activity, a number of compounds were selected for further investigation in our laboratory. The aim of this study was to investigate a novel small molecule, Compound 60 (9-[(1-methyl-3-piperidinyl)methoxy]-4-[(6-methyl-2-pyridinyl)methyl]-7-(5-methyl-2-thienyl)-2,3,4,5-tetrahydro-1,4-benzoxazepine); by monitoring (i) its effect on cancer cell biology using cervical and oesophageal cancer cell lines, (ii) its effect on nuclear import activities associated with Kpnβ1, (iii) its in vitro ADME pharmacokinetics and in vivo anti-cancer properties and (iv) performing biophysical analysis of Kpnβ1:C60 interactions. Cervical and oesophageal cancer cells were found to be more sensitive to C60 treatment compared to non-cancer epithelial cell. C60 treatment resulted in the inhibition of cancer cell proliferation, colony formation, migration and invasion. G1/S cell cycle arrest and a reduced expression of cell cycle regulatory proteins such as Cyclins D1, B1 and A as well as CDK4 was observed on treatment with C60. C60 induced cell death via apoptosis as observed PARP cleavage. These results suggest that C60 has an inhibitory effect on cancer cell biology. Immunofluorescent analysis and nucleo-cytoplasmic western blot analysis showed that C60 treatment resulted in the cytoplasmic retention of Kpnβ1. Immunofluorescent analysis and luciferase reporter assays showed that C60 inhibited the nuclear entry and transcriptional activity of a Kpnβ1 cargo, NFκB. Similarly, the transcriptional activity of cargo proteins NFAT and AP-1 were also inhibited. This suggests that C60 inhibits the nuclear entry of Kpnβ1 and thus its function as a nuclear importer of cargo proteins. In vitro ADME pharmacokinetics analysis found C60 to have high solubility, permeability and plasma protein binding properties and a short half-life. These findings suggest that C60 may have good oral absorption but rapid clearance in living systems. In vivo toxicology studies showed that C60 is tolerable, allowing for its testing in a xenograft nude mouse model. Intraperitoneal injection of C60 selectively inhibited the growth of oesophageal tumour cells with a significant effect observed on KYSE 30 oesophageal tumours. To investigate Kpnβ1:C60 binding interactions, Kpnβ1 was purified using the GST-tagged purification technique. Purified Kpnβ1:C60 interactions were monitored using the Bio-layer interferometry technique. Our preliminary data suggest an interaction between C60 and Kpnβ1 with Kd values in the micromolar range. We obtained varying Kd values, hence further optimisation is required to arrive at a conclusive Kd value. In conclusion, this study is a first to show that Compound 60 (9-[(1-methyl-3-piperidinyl)methoxy]-4-[(6-methyl-2-pyridinyl)methyl]-7-(5-methyl-2-thienyl)-2,3,4,5-tetrahydro-1,4-benzoxazepine), a small molecule identified to bind Kpnβ1 in an in silico screening approach interferes with the subcellular localisation of Kpnβ1, inhibits the localisation and transcriptional activity of Kpnβ1 cargo proteins and inhibits cancer cell biology in vitro and in vivo. In vitro ADME pharmacokinetics shows that C60 has tolerable drug properties. Biophysical analysis shows that C60 appears to bind Kpnβ1 in the micromolar range. Together, these results provide evidence for C60 as a compound that warrants further investigation as an anti-cancer agent.